Possible effects of left pulmonary artery stenting in single ventricle patients on bronchial area, lung volume and lung function - Callegari, Alessia; Geiger, Julia; Callaghan, Fraser Maurice; Kellenberger, Christian; Usemann, Jakob; Burkhardt, Barbara Elisabeth Ursula; Kretschmar, Oliver; Valsangiacomo Büchel, Emanuela (Frontiers in Pediatrics, 2024)
Background: Left pulmonary artery (LPA) stenting is often required in single ventricle (SV) patients.Due to their close anatomical relationship an LPA stent could potentially compress the left main bronchus (LMB). We assessed the impact of LPA stenting on bronchial size, pulmonary volumes, and lung function in a cohort of SV patients.Methods: Forty-nine patients underwent cardiovascular magnetic resonance (CMR) and 36 spirometry 11 (8-15) years after Fontan. All patients were free of respiratory symptoms. LPA stents were inserted in 17 (35%) patients at 8.8 (3.4-12.6) years. Area/shape of the main bronchi (n=46) and lung volumes (n=47) were calculated from CMR-ZTE images for each lung and transformed in right-to-left (r/l) ratio and indexed for BSA. The effect of early stent insertion (prior to stage III) was analyzed.Results: Patients with LPA stent had larger r/l ratio for main bronchus area (p<0.001) and r/l ratio difference for lung volumes was slightly larger in patients with early stenting. A trend toward a deformation of LMB shape in patients with LPA stent and toward a higher prevalence of abnormal spirometry in patients with early stent implantation was observed.In this cohort of patients, early insertion of LPA stents seems to relate with smaller LMB sizes and a trend toward smaller left lung volume and higher prevalence of impaired lung function. Whether these findings are caused by the stent or, at least to a certain degree, present prior to the implantation needs to be verified.